ANALISIS PENGARUH FDR, CAR, NPF, DAN BOPO TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA (STUDI KASUS BANK SYARIAH MANDIRI PERIODE 2016-2020) - Meiske Wenno (Soso-Q : Jurnal Manajemen, 2021)
AbstractThe purpose this article is to determine the effect of the influence of Financing to Deposit Ratio (FDR),  Capital  Adequacy  Ratio  (CAR),  Non  Performing  Financing  (NPF),  and  Operating Expenses and Operating Income (BOPO) on the  Profitability of Islamic Banks in Indonesia (Case Study of Islamic Banks). Independent Period 2016-2020). The sample of this research is Bank  Syariah  Mandiri.  Analysis  of  the  data  used  to  test  the  hypothesis  is  to  use  multiple regression  analysis  techniques.  The  findings  of  this  study  are  that  the  Financing  to  Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) has no effect on ROA, while the ratio of Operating Expenses and Operating Income (BOPO) has an effect on ROA. The managerial implication of this research is to encourage the bank's management to set  a  strategy  to  maximize  its  profitability  by  considering  the  capital  adequacy  ratio, financing risk and liquidity risk. Keywords – FDR, CAR NPF, BOPO